Класифікація завдань стандартизації та сучасний стан нормативної бази з питань екології в електроенергетиці - Sokolovska I.S.; Stoyanova I.I. (General Energy Institute of the National Academy of Sciences of Ukraine, 2013)
Implementation of international ecological requirements in the fuel and energy complex is a prerequisite for further integration of Ukraine into the EU. The basic EU Directives on environmental issues, which are crucial for the energy industry, are considered. Classification of standardization tasks related to emissions and operational impacts of power facilities is developed upon the basis of technical energy systems concept. The classification enables to solve the environmental problems of power industry taking into account the pollution of air, water and soil, as well as radiation and heat effects. International and national environmental standards had been analyzed on the basis of the classification, and the main tasks of standardization on ecological problems in the electricity sector of Ukraine were determined. It was proved that update of the regulatory system in the electric power industry by harmonization of national standards with European and international standards creates conditions for the greatest possible reduction of the negative impact of power facilities on the environment at all stages of production, transmission, and distribution of electricity and heat.